In situ study of Co₃O₄ morphology in the CO-PROX reaction - Khasu, Motlokoa (Centre for Catalysis Research, 2017)
The preferential oxidation (PROX) reaction is an effective process for the removal of trace amounts of carbon monoxide from a reformate stream. Tricobalt tetraoxide (Co₃O₄) is the candidate for CO-PROX in a H₂ rich gas and could be an alternative to the rare and expensive PGMs. This study investigates the effect of different Co₃O₄ morphologies in the preferential oxidation of carbon monoxide in H₂ rich gas. Reports have shown morphology dependency in CO oxidation in the absence of hydrogen, no study has investigated the morphology dependency in H₂ rich atmospheres. Different morphologies of nanocubes, nanosheets and nanobelts were prepared using hydrothermal mn and precipitation. Conventional spherical nanoparticles from our group were included to compare the activity of conventional nanoparticles with nanoparticles of different morphology. The model catalysts were supported on silica spheres which were also prepared. The CO-PROX experiments were conducted in the in situ UCT-developed magnetometer and PXRD capillary cell instruments by induced reduction at temperatures between 50 and 450°C. Catalyst tests showed two distinct temperature regions with maximum activity. In the range of 150 – 175ᵒC, activity decreased from nanoparticles > amine nanosheets > nanobelts. However, the surface area specific rate of CO₂ formation displayed an inverse trend. In the region of 225 – 250ᵒC, nanocubes > NaOH nanosheet > HCl nanocubes showed maximum activity. The surface area specific rate was the same for amine nanocubes and NaOH nanosheets. None of the model catalysts retained their morphology after the temperature was ramped from 50ᵒC to 450ᵒC, and back to 50ᵒC. The catalysts were partially reduced to metallic Coo (other phase being CoO). Figure 1: In situ PXRD analysis and kinetics of CH4, CO and CO₂ showing the behaviour of Co₃O₄/SiO₂ (amine nanocubes) under CO-PROX conditions